Reduced Versus Conventional Dose Insulin for Hyperkalemia Treatment. (June 2020) - Garcia, Joshua; Pintens, Megan; Morris, Amanda; Takamoto, Paul; Baumgartner, Laura; Tasaka, Chelsea L.
Background: Using a reduced dose of 5 units of regular insulin has been proposed as a strategy to mitigate the risk of hypoglycemia when treating hyperkalemia. The comparative efficacy and safety of this strategy to conventional 10 units is not well established. Objective: To compare the effectiveness of reduced and conventional dosed insulin for hyperkalemia treatment. Methods: Electronic medication administration reports of conventional or reduced doses of insulin given for hyperkalemia treatment were reviewed from July 2013 to September 2015. The primary outcome was reduction in serum potassium. Results: Ninety-two administrations of reduced dose insulin and 309 administrations of conventional dose insulin were included. No significant difference was found in potassium reduction between the groups (−0.096 mmol/L, P value = .2210). Post hoc subgroup analysis of patients with serum potassium > 6 mmol/L revealed a lower reduction in potassium in the reduced dose group compared to the conventional dose group (difference: −0.238 mmol/L, P value = .018). Conclusions: Conventional dose insulin may be more effective than reduced dose regular insulin at baseline serum potassium levels >6 mmol/L in the treatment of hyperkalemia. Frequent monitoring of serum potassium and glucose after administration of insulin is necessary to confirm adequate response and avoidance of hypoglycemia.